2004
DOI: 10.1152/ajpheart.01046.2003
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous obesity is not associated with sympathetic neural activation

Abstract: We tested the hypothesis that muscle sympathetic nerve activity (MSNA) would not differ in subcutaneously obese (SUBOB) and nonobese (NO) men with similar levels of abdominal visceral fat despite higher plasma leptin concentrations in the former. We further hypothesized that abdominal visceral fat would be the strongest body composition- or regional fat distribution-related correlate of MSNA among these individuals. To accomplish this, we measured MSNA (via microneurography), body composition (via dual-energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
3
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 46 publications
7
76
3
6
Order By: Relevance
“…The results clearly indicate that the degree of sympathetic activation (and the magnitude of the insulin resistance state) is much greater in patients with visceral body fat deposits than in those with peripheral distribution of the adipose tissue. This finding (which, as discussed below, underscores once again the close relationships between sympathetic overactivity and insulin sensitivity) has been further confirmed by the results of a study showing that subcutaneous body fat accumulation is not linked to an adrenergic overdrive (21).…”
Section: Sympathetic Function In Hypertension and In Obesitysupporting
confidence: 58%
“…The results clearly indicate that the degree of sympathetic activation (and the magnitude of the insulin resistance state) is much greater in patients with visceral body fat deposits than in those with peripheral distribution of the adipose tissue. This finding (which, as discussed below, underscores once again the close relationships between sympathetic overactivity and insulin sensitivity) has been further confirmed by the results of a study showing that subcutaneous body fat accumulation is not linked to an adrenergic overdrive (21).…”
Section: Sympathetic Function In Hypertension and In Obesitysupporting
confidence: 58%
“…Secondly, leptin has been proposed to activate the sympathetic nervous system in animals, 44 although in humans, the levels of plasma leptin have been reported to be related to heart rate in men only and in general to obesity but not to sympathetic nerve activity. 45,46 However, the four groups of the present study had similar BMI, waist circumference and heart rate. Thirdly, there are obvious differences in the plasma levels of sex hormones between women and men, and these have been tested in relation to MSNA.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 53%
“…Therefore, altered cytokine production may underlie the strong association between visceral fat and sympathetic activation. However, some studies have shown that leptin is more related to total or subcutaneous fat rather than to visceral fat (32,34). If this is true, direct stimulation of the central nervous system by leptin could not explain our finding that visceral fat is strongest associated with sympathetic activation.…”
Section: Tablementioning
confidence: 57%
“…Two of these papers also investigated SAT and reported that VAT was stronger associated with sympathetic activation than SAT (32,33). Another study reported that sympathetic activation in individuals with high subcutaneous fat was not different from nonobese individuals (34). We were able to extend these observations by showing that VAT was also associated with measures of sympathetic activation on the ECG (HR, QTc, and the ventricular gradient) after adjustment for SAT, while the association of SAT with these measures attenuated after adjustment for VAT.…”
Section: Tablementioning
confidence: 99%